Improving e-learning system using automated document downloading and announcement delivery - Hasan, Mohd Hilmi; Haron, Nazleeni Samiha; Hassan, Mohd Fadzil; Jusoff, Kamaruzaman; Shahrom, Fazlina; Roslan, Nabila Syanaz (IDOSI Publications, 2011)
The rapid advancement of information technology has led to an explosive expansion of web-based learning. Numerous academic institutions have implemented e-learning system for not just supporting distance learning, but also for their conventional mode of teaching delivery namely for discussion, sharing materials and posting announcement. The objective of this paper is to present the improvement of current e-learning systems that require students to manually download teaching materials and check for new announcements posted by instructors. The system is developed in three-tier architecture and tested using functional testing. The system is installed on student’s computer and has timer feature which instructs server to perform the checking procedures to look for new documents and announcements for every scheduled period of time. Any new documents and announcements will be automatically downloaded to student’s computer. The system is successfully developed and believed can improve the e-learning system. The study implies potential time saving as students do not have to manually check for new course document and announcement posted by instructors in e-learning. For future works, it is proposed that push technology is implemented to initiate the process of checking new document and announcement from server, which can reduce the use of network resources.